Development of Full-Scale Ultrathin Shell Reflector - Durmuş Türkmen; Ömer Soykasap; Şükrü Karakaya (International Journal of Antennas and Propagation)
It is aimed that a new ultrathin shell composite reflector is developed considering different design options to optimize the stiffness/mass ratio, cost, and manufacturing. The reflector is an offset parabolic reflector with a diameter of 6 m, a focal length of 4.8 m, and an offset of 0.3 m and has the ability of folding and self-deploying. For Ku-band missions a full-scale offset parabolic reflector antenna is designed by considering different concepts of stiffening: (i) reflective surface and skirt, (ii) reflective surface and radial ribs, and (iii) reflective surface, skirt, and radial ribs. In a preliminary study, the options are modeled using ABAQUS finite element program and compared with respect to their mass, fundamental frequency, and thermal surface errors. It is found that the option of reflective surface and skirt is more advantageous. The option is further analyzed to optimize the stiffness/mass ratio considering the design parameters of material thickness, width of the skirt, and ply angles. Using the TOPSIS method is determined the best reflector concept among thirty different designs. Accordingly, new design can be said to have some advantages in terms of mass, natural frequency, number of parts, production, and assembly than both SSBR and AstroMesh reflectors.